2012
DOI: 10.1186/1748-5908-7-92
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of hand hygiene improvement strategies: a behavioural approach

Abstract: BackgroundMany strategies have been designed and evaluated to address the problem of low hand hygiene (HH) compliance. Which of these strategies are most effective and how they work is still unclear. Here we describe frequently used improvement strategies and related determinants of behaviour change that prompt good HH behaviour to provide a better overview of the choice and content of such strategies.MethodsSystematic searches of experimental and quasi-experimental research on HH improvement strategies were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
203
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(221 citation statements)
references
References 72 publications
3
203
0
15
Order By: Relevance
“…However, despite the widely recognised importance of hand hygiene, considerable investment by governments, organisations and health facilities, and that hand-hygiene is a relatively simple act particularly with the availability of agents such as alcohol hand-rub, health care workers' compliance with best practice has historically been variable (<40% to approximately 80% on average internationally) [10][11][12]. While research has been conducted in recent years to identify the most effective strategies for improving hand hygiene compliance [13,14], a systematic review concluded that there is a dearth of high quality, robust evidence demonstrating which interventions are the most effective for improving and sustaining hand hygiene compliance [13]. Furthermore, "there remains an urgent need to undertake methodologically robust research" [13].…”
mentioning
confidence: 99%
“…However, despite the widely recognised importance of hand hygiene, considerable investment by governments, organisations and health facilities, and that hand-hygiene is a relatively simple act particularly with the availability of agents such as alcohol hand-rub, health care workers' compliance with best practice has historically been variable (<40% to approximately 80% on average internationally) [10][11][12]. While research has been conducted in recent years to identify the most effective strategies for improving hand hygiene compliance [13,14], a systematic review concluded that there is a dearth of high quality, robust evidence demonstrating which interventions are the most effective for improving and sustaining hand hygiene compliance [13]. Furthermore, "there remains an urgent need to undertake methodologically robust research" [13].…”
mentioning
confidence: 99%
“…Another review by Huis et al reported in 2012 was conducted but with a focus on classifying the improvement activities based on their determinants of behavior change 7 . It was stated in the review that the criteria for inclusion were not as stringent as Gould et al 6 but rather the standards of Anderson and Sharpe were used 8 .…”
mentioning
confidence: 99%
“…It is likely that this The review provides a useful descriptive account of the geographical locations and clinical settings of the included studies. In line with the findings of previous reviews (3,6,7), the selected studies focus primarily on hand hygiene practices of nurses, doctors and healthcare assistants, highlighting a continuing omission of other health care…”
Section: Accepted Manuscriptmentioning
confidence: 84%